Sustainability of dairy systems through the lenses of the sustainable development goals - Wattiaux, Michel A. (Frontiers in Animal Science, 2023)
In this paper, we propose to view the sustainability of dairy farming as nested within the sustainability of agriculture, a subset of the sustainability of food systems, which in turn could be construed as a subset of the national commitments of a country to achieve the Sustainable Development Goals (SDGs). Disciplinary, multidisciplinary, and interdisciplinary research are essential to study bio-physical system components and their interactions. However, when dairy farming is viewed as nested within broader societal systems, the inclusion of human elements calls for transdisciplinary research. Few of the 17 SDGs are left untouched by the livestock sector. Research should aim at identifying relevant farm-level metrics that are in alignment with any of the 231 indicators supporting the SDGs. We used two examples to illustrate the approach. In the first, SDG 13 (Climate Action) is used as a reminder that despite the current emphasis on reducing milk carbon footprint (kg CO2-e/kg milk), the contribution of the sector to Climate Action depends on reducing its annual emission (kg CO2-e/year; indicator 13.2.2). In the second example, indicator 2.4.1 (land use for sustainable agriculture) of SDG 2 (Zero Hunger) is used to illustrate the potential tradeoff between Milk N / Intake N as a metric of nitrogen use efficiency at the cow level and metrics such as the input:output ratio of human-edible protein (Milk N / Intake of Human-edible N) that prioritize the use of human-inedible feed in dairy rations as a way to enhance efficiency and circularity at the food system level.